Dengue fever in returned Swedish travelers from Thailand - Tuiskunen, Anne (Co-Action Publishing, 2011)
The dengue viruses (DENV) are endemic in the tropical and sub-tropical countries and cause the most common arthropod-borne viral disease in humans. Travelers visiting endemic areas may both acquire and spread DENV infections, and this is the reason why prevention of mosquito bites is of crucial importance. Dengue fever (DF) has become the most common cause for tropical fever in Swedish tourists. Swedish data from 1995 to 2010 show that the number of DF cases has increased since the beginning of 2000; partly due to improved diagnostics based on IgM detection, and partly due to an increase in the number of tourists traveling to, and between, endemic areas. Young adults aged 20–29 are mostly affected, and epidemiological data indicate increased incidence rates from 2008 onwards. Our data pose a call for attention when traveling to DENV endemic areas as well as an increased awareness among physicians when treating returning travelers.